Optimization of the cyclotide framework to improve cell penetration properties - Huang, Yen-Hua; Chaousis, Stephanie; Cheneval, Olivier; Craik, David J.; Henriques, Sónia T. (Frontiers in Pharmacology, 2015)
Cell penetrating peptides have been regarded as promising vectors to deliver hydrophilic molecules inside cells. Although they are great tools for research and have high potential as drug delivery systems, their application as drugs is impaired by their low stability in serum. Cyclotides, cyclic disulfide-rich peptides from plants, are ultra-stable molecules that have inspired applications in drug design as they can be used as scaffolds to stabilize linear bioactive sequences. Recently, they have also been shown to possess cell-penetrating properties. The combination of their remarkable stability and cell-penetrating properties opens new avenues for the application of peptides to bind to and inhibit intracellular proteins. Nevertheless for a broader application of these molecules as vectors is of utmost importance to improve their cellular internalization efficiency. In this study we successfully modified MCoTI-II, one of the most widely studied cyclotide scaffolds in drug design, and improved its internalization properties. The internalization of the newly designed MCoTI-II is as efficient as the gold standard cell-penetrating peptide TAT and maintains all the required features as a template to graft desired bioactivities.